It is hereby performed-- : explorations in legal speech acts - Kurzon, Dennis (Pragmatics & beyond ;, 1986)
This book deals with speech acts, especially performatives, that are regarded as 'operative' in legal discourse. After a detailed exposition of speech act theory in relation to legislative texts, the author discusses the legal document as a communicative act; potential speech acts and delegated legislation; wills, the marriage ceremony and statutes as reversible performatives; and the distinction between the deictic function of this and the anaphoric function of that in legal documents. The final chapter is concerned with another text type, case reports, and addresses the questio.